From presentation to debate: the change in the national assembly of Vietnam - Nguyen, Dang Dung (Đại học Quốc gia Hà Nội, 2020)
By analysing the change in the parliamentary activities of the Vietnam National Assembly since its establishment (1946), the authors state that before “Doi Moi” (Innovation, 1986), National Assembly of Vietnam‘s activity in congress was mainly “presentation” (tham luận), in which the selected delegates present (often reading) the ideas that they have prepared beforehand about the issues raised at the parliament, in order to illustrate and explaine related guidelines and policies of the Communist Party. Since Doi Moi, the parliamentary activity of the Vietnam National Assembly has increasingly shifted from “presentation to debate”. Besides achievements, the National Assembly also faces certain difficulties in this regard. In this paper, the authors assess the changes in National Assembly’s activities since Doi Moi as well as pointing out challenges in order to recommend solutions to solve these problems.